ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN MAHASISWA - Agus Dwi Atmoko (Politeknik Sawunggalih Aji, 2018)
The Quality of a college is influenced by students’ satisfaction. The increasing of students’ satisfaction playsan important role in improving the quality of a College. Because students are the key for college to get the profit and tosurvive. The Quality of College or organization is determined on how students views the organization, therefore oneorganization has to understand what the students desire for current and future by satisfying students’ desire and moreoveran organization should exceed their expectation. The quality improvement is the key to success, because satisfaction is afunction of performance and expectations. If performance is below expectations, the customer is not satisfied. But if theperformance meets expectations, the customer is satisfied. Today many universities focusing on high satisfaction because when students only get satisfaction they will easilychange their mind to get the better offer. They who are very satisfied will be a tough one to change their mind. Highsatisfaction creates an emotional attachment to the brand, not just a rational preference. The population of the research are students of Polytechnic Sawunggalih Aji. The population consists of Threedifferent programs namely Accounting, Information Technology and Business Administration in April 2015 amounted to393 students. Samples taken are 80 Polytechnic Sawunggalih Aji’s students. From the research result the level of student satisfaction on the quality indicators in the Customer Satisfactioncategory are satisfied. It is shown from the majority of students are satisfied as much as 33.78. The level of studentsatisfaction at Tangibles indicators are in the category satisfied. It is shown from the majority of students are satisfied.Tangibles variable regression coefficient (X1) of 0.121. The level of student satisfaction on Reliability indicators are inthe category satisfied. It is shown from the majority of satisfied students’ regression coefficient Reliability (X2) is 0,139. The level of student satisfaction at Responsiveness indicators are in the category satisfied. It is shown from themajority of students are satisfied. The regression coefficient variable Responsiveness (X3) at 0, 275. The level of student satisfaction on Assurance indicators are in the category satisfied. It is shown from themajority of students are satisfied. Assurance variable regression coefficient (X4) of 0.304. The level of student satisfactionat Empathy indicators are in the category satisfied. It is shown from the majority of students are satisfied as variableregression coefficient Empathy (X5) of 0,071.